AN ETHNOBOTANICAL STUDY OF MEDICINAL PLANTS USED IN VILLAGES UNDER JONGILANGA TRIBAL COUNCIL, MPUMALANGA, SOUTH AFRICA - Tshikalange, Thilivhali Emmanuel; Mophuting, Boikanyo Calvin; Mahore, James; Winterboer, Stefan; Lall, Namrita (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Medicinal plants remain an integral part of the lives of people in rural areas. The aim of this study was to document information about the medicinal plants used by Shangaan people in villages under Jongilanga tribal council, Bushbuckridge municipality, Mpumalanga Province, South Africa. Materials and Methods: An ethnobotanical survey of medicinal plants was conducted using a semi-structured questionnaire with 15 traditional healers as informants; one of them also served as a field guide during data collection. Results were analysed by using various quantitative indices of information consensus factor (ICF), use report (UR), frequency citation (FC) and relative frequency citation (RFC). Results and Methods: The study reported 86 medicinal plants used in villages for the treatment of various ailments, the majority (25 species) of which were used for urino-genital disorders. The Fabaceae family was the most represented family (17 species) of all the medicinal plants recorded in this study. The roots were the most frequently used plant part, accounting for 56% of the plants reported, and decoctions were often used in the preparation of herbal remedies. Respiratory diseases had the highest ICF value recorded among the 8 categories of ailments. The highest use report was reported for Combretum collinum (4), while the FC and RFC values (15) were highest in 12 plant species. The study revealed that medicinal plants are still widely used in rural areas and this documentation can serve as an ethno pharmacological basis for selecting plants with potential pharmaceutical properties.